1980
DOI: 10.1111/j.1745-4565.1980.tb00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosamines in Alcoholic Beverages

Abstract: A limited survey was carried out to determine the nitrosamine content of several varieties of alcoholic beverages (beer and ale, whiskey, wine, cider, etc.) sold in Canada. Of 22 samples of different beers and ales analyzed all but one contained traces of dimethylnitrosamine; the overall mean level found was 1.5 ppb. Only one Canadian rye and one Scotch whiskey out of a total of 13 samples contained traces of either dimethylnitrosamine or diethylnitrosamine. All the 8 wines and 7 cider samples were negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…As a consequence considerable effort has gone into determining whether these compounds occur in the diet. Analytical methods for volatile Af-nitrosamines are well established and it is known that these compounds may occur in trace amounts in products such as beer (Sen et al 1980, Massey et al 1990 and cured meats (Gray et al 1982, Vecchio et al 1986). Procedures for non-volatile N-nitroso compounds are less well advanced although methods have been developed for certain classes such as the N-nitrosoamino acids (Sen et al 1983, Tricker etal.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence considerable effort has gone into determining whether these compounds occur in the diet. Analytical methods for volatile Af-nitrosamines are well established and it is known that these compounds may occur in trace amounts in products such as beer (Sen et al 1980, Massey et al 1990 and cured meats (Gray et al 1982, Vecchio et al 1986). Procedures for non-volatile N-nitroso compounds are less well advanced although methods have been developed for certain classes such as the N-nitrosoamino acids (Sen et al 1983, Tricker etal.…”
Section: Introductionmentioning
confidence: 99%
“…While both beer and liquor have been reported to contain mutagens [Sen et al, 1980;Walker et al, 19791, only one of these products tested in this study showed any mutagenic potential. Nitrosamines commonly found in alcoholic beverages at ppb levels would not be detected because of their low concentration and volatility and the lack of a liquid pre-incubation step in the standard Salmonella assay [Ames et al, 19751.…”
Section: Discussionmentioning
confidence: 78%
“…Vacuum Distillation Method. The technique was similar to that published previously (Sen et al 1980a) with the exception that a smaller sample size (20-25 g) was used And the sample was distilled from 1% sulfamic acid instead of from 3 N KOH solution. The rest of the procedure was exactly as described before (Sen et al 1980a).…”
Section: Determination Of Dmnmentioning
confidence: 99%
“…The technique was similar to that published previously (Sen et al 1980a) with the exception that a smaller sample size (20-25 g) was used And the sample was distilled from 1% sulfamic acid instead of from 3 N KOH solution. The rest of the procedure was exactly as described before (Sen et al 1980a). The replacement of 3N KOH with 1% sulfamic acid as the distillation medium gave improved and more consistent recovery (== 80%) of DMN from beer and ale, and also reduced the chance of artefactual formation, if any, of nitrosamines during distillation (Sen et al 1980b;Pignatelli et al 1980).…”
Section: Determination Of Dmnmentioning
confidence: 99%
See 1 more Smart Citation